Empowerment of adolescent girls in India : perspective, issues, and approaches - Singh, Awadhesh Kumar; Pandey, S. P., 1958-; Singh, Atul Pratap (New Delhi : Serials Publications, 2011)
Papers presented at a national seminar on Empowerment of adolescent girls in India, held at Lucknow during 6-7 June 2010.
Includes bibliographical references.
Keywords: sociology; Teenage girls -- India -- Economic conditions -- Congresses; Teenage girls -- Health and hygiene -- India -- Congresses